Impact Analysis of the Israel-Hezbollah Conflict on the Security of Lebanese Civil Society: A Case Study of the 2024 Beeper Explosion in South Lebanon - Aullya Ananda Putri; Yanuar Rahmadan (Universitas Tribhuwana Tungga Dewi, 2025)
Israel and Hezbollah have been in conflict since 1982, followed by another conflict in 2006. In 2024, there was a pager explosion in Lebanon, with Israel reportedly behind it, placing explosives in pagers and walkie talkie communication devices used by Hezbollah members. This research uses a qualitative research method with a descriptive approach to analyze the impact of the 2024 pager explosions in Lebanon on the security of civilians in Southern Lebanon. Using the Human Security Theory, this study discusses the human rights of individuals and the legal basis in armed conflict. This research shows that the security of civilians in Lebanon isÂ Â threatened in the occurance of pagers and walkie talkie explosions. individuals have been granted on their human rights through various human rights legal frameworks, although in reality violations continually occur especially during conflicts, hence human security could not be fully ensured.Konflik antara Israel dan Hezbollah telah berlangsung sejak tahun 1982, kemudian berlanjut dengan konflik berikutnya pada tahun 2006. Pada tahun 2024, terjadi ledakan pager di Lebanon, di mana Israel diduga bertanggung jawab dengan menempatkan bahan peledak pada pager dan perangkat komunikasi walkie talkie yang digunakan oleh anggota Hezbollah. Penelitian ini menggunakan metode kualitatif dengan pendekatan deskriptif untuk menganalisis dampak ledakan pager 2024 di Lebanon terhadap keamanan masyarakat sipil di Lebanon Selatan. Dengan menggunakan Teori Keamanan Manusia, studi ini membahas hak asasi individu dan dasar hukum dalam konflik bersenjata. Hasil penelitian menunjukkan bahwa keamanan masyarakat sipil di Lebanon terancam akibat ledakan pager dan perangkat komunikasi tersebut. Meskipun hak asasi manusia telah dijamin melalui berbagai kerangka hukum hak asasi manusia, pelanggaran terus terjadi, terutama selama masa konflik, sehingga keamanan manusia tidak dapat sepenuhnya terjamin.